Caracterización fisicoquímica del suero lácteo de las industrias queseras del cantón Latacunga - Tercero Tercero, Jessica Paulina (2023)
The current investigative work has as approach on the whey physicochemical characterization from 32 cheeses factories from Latacunga canton, in order to generate alternatives for the agro-industrial exploitation this valuable by-product resultant from cheeses production this canton. Into this study, it was made a cheese industries general diagnosis from Latacunga canton was carried out in the first instance, followed by the taking dairy whey samples each one the cheese industries by using the methodology established in the Ecuadorian Technical Standard NTE INEN 4, and finally, the physicochemical analyzes application, such as pH, acidity, density (ρ), fat amount (g), non-fatty solids (SNG) and water amount; using the LACTOSCAN SLP equipment and the NTE INEN 13 methodologies for the pH and NTE INEN 2594:2011, determination for the acidity determination. Finally, the got results were compared with the INEN 2594:2011 Standard, allowing the whey classification into sweet or acid based on its pH and acidity. Given as result, what the analyzed 32 samples, 20 samples are classified as sweet whey and 12 samples as acid whey, in accordance to their pH; and regarding acidity, 18 samples are classified as sweet whey and 11 samples as acid whey. Therefore, the compiled results reflect, which the 32 cheese factories whey analyzed from Latacunga canton are very good quality and they can be used to got derived products within the food industry with added value, thus maximizing, economic gains within this sector and minimizing the disposal environmental impact this by-product in the means.